2022
DOI: 10.2147/idr.s376413
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Colonization with Carbapenem-Resistant Enterobacteriaceae in Acute Leukemia Patients: Risk Factors and Molecular Characteristics

Abstract: Background Carbapenem-resistant Enterobacteriaceae (CRE) colonization is associated with bacterial translocation, which can result in subsequent endogenous CRE infection. In the present study, we aim to investigate the colonization-related risk factors and molecular epidemiological characteristics of CRE in patients with acute leukemia. Methods From January 2021 to December 2021, acute leukemia patients were screened for CRE by fecal/perianal swabs. We identified the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…However, the rate in China was lower than the rate of 75.5% reported in India ( 14 ). Additionally, single-center studies in China have reported CRE colonization rates ranging from 6.6% to 23.8% in patients with hematologic malignancies ( 15 , 16 ). Among all colonized CR-GNB isolates, CRE colonization accounted for the highest, followed by CRPA, while CRAB colonization was rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate in China was lower than the rate of 75.5% reported in India ( 14 ). Additionally, single-center studies in China have reported CRE colonization rates ranging from 6.6% to 23.8% in patients with hematologic malignancies ( 15 , 16 ). Among all colonized CR-GNB isolates, CRE colonization accounted for the highest, followed by CRPA, while CRAB colonization was rare.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies on CRE colonization have focused on hematologic diseases and ICU populations, and the results have varied widely. For example, CRE colonization rates were reported as 1.5–75.5% in hematological malignancy patients [ 17 , 20 ]. CRKP is the most common CRE species [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, colonization could be an important source of transmission. Active screening for CRE colonization will help control its spread [ 16 , 17 , 18 ]. A German study showed that colonization with MDR bacteria increases mortality in patients with ESLD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRE intestinal colonization can increase the incidence of CRE infection in patients with acute leukemia [ 11 ]. CrKP accounts for approximately 60% of CRE infections in China [ 12 ].…”
Section: Discussionmentioning
confidence: 99%